2020
DOI: 10.1017/sus.2020.20
|View full text |Cite
|
Sign up to set email alerts
|

Corona and the climate: a comparison of two emergencies

Abstract: Social media summary Lessons from the corona crisis can help manage the even more daunting challenge of anthropogenic global warming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Furthermore, the pandemic has shown that good air quality is essential for avoiding severe health outcomes from the pandemic. The current health emergency has also provided a glimpse of the potential climate emergency in the absence of climate action (Vinke et al., 2020). Another crucial lesson of the pandemic is to promote South‐South cooperation, that is, more exchange of resources, technologies, and knowledge with other developing countries, together with North‐South cooperation, that is, obtaining economic and other forms of support from developed countries (SDG 17).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the pandemic has shown that good air quality is essential for avoiding severe health outcomes from the pandemic. The current health emergency has also provided a glimpse of the potential climate emergency in the absence of climate action (Vinke et al., 2020). Another crucial lesson of the pandemic is to promote South‐South cooperation, that is, more exchange of resources, technologies, and knowledge with other developing countries, together with North‐South cooperation, that is, obtaining economic and other forms of support from developed countries (SDG 17).…”
Section: Resultsmentioning
confidence: 99%
“…By exposing the vulnerability of contemporary supply chains, the pandemic has led many companies to fundamentally question the dominant supply chain narrative of cost reduction and responsiveness. The pandemic has succeeded in getting people to ask the questions they have failed to ask about other serious issues, including the much more existential climate and biodiversity crises (see Pagell & Shevchenko, 2014; Vinke et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…All of these activities are linked to further long-term research as well as the need for urgent and immediate action. Lessons from the COVID-19 pandemic can help to tackle future pandemics as well as other global emergencies ( Vinke et al, 2020 ). Recovery measures will need to be assessed for their short- and long-term effects on the drivers of potential pandemics, and it is important to keep track of constantly emerging results of research on COVID-19 and global environmental change to be able to link them to new research questions aligned with societal needs.…”
Section: Discussionmentioning
confidence: 99%